Implementation of Dolanan Bocah to Improve Factual Speaking Ability of Primary School Students - Biya Ebi Praheto (Intelektual Pustaka Media Utama, 2018)
This research aims to improve the factual speaking ability of the 5th grade students of SD Negeri Mendungan 2 Yogyakarta by implementing dolanan bocah (traditional game) in the learning. This is a classroom action research conducted in two cycles. The subject of this action research is the 5th students of SD Negeri Mendungan 2 Yogyakarta in the academic year 2015/2016. There are 30 students consisting of 16 female and 14 male students. This study differs from previous ones. This can be seen from the research action that integrates dolanan bocah in learning speaking Bahasa Indonesia. The implementation of dolanan bocah gives significant improvement on the students’ factual speaking ability. The improvement can be shown from the scores obtained in the cycle I and II. In the first cycle, the average score is 71.9 with the classical completeness of 63.3%, while in cycle II, there is an increased average score of 82.4 with the classical completeness of 83.3%.